Continuous forming process of wet-process multilayer composite material
Through the continuous forming process of wet multilayer composite materials, using nano-scale interface processing and roll-to-roll continuous production line, the problems of weak interlayer bonding force, low production efficiency and high energy consumption in the prior art are solved, and the effects of high performance, efficient production and low energy consumption are achieved.
Patent Information
- Application Number
- CN202411947937.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing multi-layer composite material preparation technology has problems such as weak interlayer bonding force, low production efficiency and high energy consumption, which seriously limits its wide application and industrial development in various fields.
The new continuous molding process of wet multi-layer composite materials is adopted, and through nano-scale interface processing technology, roll-to-roll continuous production line design and optimized drying and curing process, the interlayer bonding force is improved, efficient production is achieved and energy consumption is reduced.
It significantly improves the performance and production efficiency of composite materials, reduces production costs and energy consumption, solves the problems of poor interlayer bonding force, low production efficiency and high energy consumption, and has broad application prospects and important industrial value.
Smart Images

Figure CN119871917A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material forming technology, in particular to a continuous forming process of a wet-process multi-layer composite material. Background Art
[0002] With the rapid development of modern industry, multilayer composite materials have been increasingly widely used in aerospace, automobile manufacturing, electronic equipment, construction and many other fields due to their excellent properties of integrating multiple materials. However, in the process of its widespread application, the existing multilayer composite material preparation technology faces many severe challenges, which seriously restricts the further development and promotion of this technology.
[0003] In terms of interlayer bonding, traditional multilayer composite materials generally have serious defects. Due to the lack of effective interlayer reinforcement means, the layers rely only on simple physical contact or weak chemical bonding, resulting in extremely weak interlayer bonding. In actual use, this weak bonding force is difficult to withstand complex external forces, which can easily lead to delamination and shedding. For example, in aircraft structural components in the aerospace field, if interlayer delamination occurs in multilayer composite materials, it will greatly reduce the overall strength and stability of the structure, posing a serious threat to flight safety; in the field of automobile manufacturing, if interlayer shedding occurs in multilayer composite materials used in automobile body parts, it will not only affect the appearance quality of the car, but also reduce its mechanical properties, shorten its service life, and increase maintenance costs.
[0004] Production efficiency and continuity are also bottlenecks in existing multi-layer composite material preparation technologies. Traditional preparation processes often rely on intermittent operations, and it is difficult to achieve seamless connections between various production links, requiring a lot of manual intervention and transfer processes. This not only leads to lengthy and cumbersome production processes, but also severely limits the increase in production speed. For example, on some traditional multi-layer composite material production lines, each time a layer of material is composited, it is necessary to stop the machine for material adjustment, equipment parameter reset, and other operations, making the entire production process time-consuming and labor-intensive, and unable to meet the urgent needs of large-scale industrial production for efficient and rapid production. This inefficient production method not only increases production costs, but also reduces the market competitiveness of enterprises, hindering the widespread popularity of multi-layer composite materials in the market.
[0005] In addition, high energy consumption is another prominent problem of existing multilayer composite material preparation technology. Traditional processes usually use conventional heating methods in key links such as drying and curing, such as hot air heating and oven heating. These heating methods have low thermal efficiency, and a large amount of heat is lost to the surrounding environment during the transfer process and cannot be effectively utilized. In order to achieve the expected drying and curing effects, a large amount of energy is often consumed, which undoubtedly further increases the production cost burden of enterprises. In the current global context of advocating energy conservation, emission reduction and sustainable development, this high-energy consumption production method is obviously contrary to the requirements of the development of the times, and a new, low-energy consumption preparation process is urgently needed to replace it.
[0006] In summary, the existing multi-layer composite material preparation technology has many problems in terms of interlayer bonding, production efficiency and energy consumption, which seriously restricts its wide application in various fields and the further development of the industry. Therefore, the development of a new wet multi-layer composite material continuous molding process that can effectively solve these problems has extremely important practical significance and broad market prospects. Summary of the invention
[0007] The present invention aims to overcome the defects of the prior art and provide a new process for continuous molding of wet multilayer composite materials. Through innovative technical means, the interlayer bonding strength of multilayer composite materials is effectively improved, continuous and efficient production is achieved, and energy consumption and production costs are reduced, thereby promoting the wide application and industrial development of multilayer composite materials in many fields.
[0008] (I) Nanoscale interface processing
[0009] Nanosol preparation and spraying
[0010] Selection and pretreatment of inorganic nanoparticles: Carefully select high-purity silica and alumina nanoparticles prepared by gas phase method, with particle size precisely distributed in the range of 20-50nm. These nanoparticles are placed in a vacuum oven and dried at 120℃ for 4 hours to completely remove surface adsorbed water and significantly improve their compatibility with polymers.
[0011] Selection and preparation of organic polymer: Highly acetalized (99%) polyvinyl alcohol (PVA, degree of polymerization 1700, degree of alcoholysis 88%) was selected and prepared into a 5wt% aqueous solution. Cross-linking agent glutaraldehyde was added to the PVA solution to promote the curing of the interface layer and enhance the bonding strength and water resistance.
[0012] Nanosol preparation and homogenization: Pretreated SiO2 and Al2O3 nanoparticles were uniformly mixed in a mass ratio of 1:1, and then slowly added to the PVA solution, strictly controlling the solid content to 10wt%. Subsequently, a high-speed disperser was used for shearing at 10,000 rpm for 30 minutes to obtain a uniform and stable nanosol dispersion.
[0013] Design and parameter optimization of automated spraying device: A six-axis robot arm and a multi-axis linkage spray gun guided by machine vision are used to precisely spray the substrate surface. The optimized spraying process parameters are: nozzle diameter 0.3mm, atomization air pressure 0.4MPa, liquid flow rate 30mL / min, and gun distance 100mm from the substrate. Through this step, a loose and porous nanostructure is formed on the surface of the substrate layer, laying the foundation for the subsequent enhancement of interlayer bonding.
[0014] Electrospinning introduces nanofibers
[0015] Selection and preparation of spinning polymer materials: Nylon 6 chips with a melting point of 225°C were used to prepare a hexafluoroisopropanol solution with a concentration of 15wt%, and 1wt% of hexadecyltrimethylammonium bromide (CTAB) was added as a conductive additive to effectively improve the spinning performance of the solution.
[0016] Design and improvement of electrospinning equipment: We designed a coaxial electrospinning device with a unique structure of inner spinning liquid and outer high-pressure air, which work together to form a stable composite jet. At the same time, we use a double-ring tube current collector, with the inner tube guiding the fiber deposition and the outer tube sucking out excess fibers, which greatly improves the deposition efficiency.
[0017] Optimization and control of electrospinning process parameters: The spinning voltage (15-30kV), receiving distance (10-20cm) and solution flow rate (0.5-2mL / h) were optimized through orthogonal experiments. The jet carving and fiber morphology were monitored in real time with a high-speed camera to ensure that the nanofiber layer was uniformly and continuously introduced into the nanostructure, so that the substrate layer and the functional layer could be tightly combined at the nano interface, significantly improving the bonding strength.
[0018] Functional layer and interface layer composite
[0019] Functional coating formula design and preparation: According to different application scenarios and requirements, flexibly select UV-curable acrylate, epoxy resin organic coating system or ITO, ZnO inorganic coating system. Use the scraper method to prepare a functional coating with a thickness of 1-10μm on the PET base film, which is used for the subsequent composite process with the interface layer after drying and curing.
[0020] Optimization of hot pressing composite process parameters: A hot roller pressing composite machine is used for composite operation. By accurately controlling the key parameters of roller pressing (1-5MPa), temperature (80-130℃) and vehicle speed (1-5m / min), and ensuring the contact time is 5-20s, continuous hot pressing composite of the functional layer and the interface layer is achieved, further strengthening the interlayer bonding force and overall performance.
[0021] Characterization and evaluation of composite interface performance: Scanning electron microscopy (SEM) and atomic force microscopy (AFM) are used to carefully observe and analyze the microstructure and roughness of the composite interface. At the same time, 180° peeling test and tensile shear test are carried out to accurately and quantitatively evaluate the interlayer bonding strength to ensure that it can reach a high standard of more than 20N / cm, thereby ensuring the quality and performance stability of the composite material.
[0022] (II) Design of roll-to-roll continuous production line
[0023] Automatic coil feeding and tension control system
[0024] Design and optimization of unwinding device: electromagnetic powder brake and servo motor work together to achieve precise control of unwinding tension, and strictly limit the tension fluctuation within ±2%. At the same time, it is equipped with advanced deviation correction device and air shaft to effectively ensure the coaxiality of the coil and the stability of the axial position during the unwinding process, ensuring the continuity and stability of the entire production process.
[0025] Guide roller system design: The unique Archimedean spiral arrangement of guide rollers cleverly achieves 90° steering and S-type tensioning of the coil. The surface of the guide roller is coated with polyurethane elastomer, and the hardness is controlled between ShoreA50-80, which can effectively prevent the coil from slipping during transmission and avoid damage to the coil, thus ensuring the surface quality and integrity of the coil.
[0026] Synchronous transmission and control solution: Use electronic gear synchronous control system to achieve speed synchronization and phase synchronization of substrate roll and functional layer roll. Among them, the speed synchronization error is less than 0.1%, and the phase synchronization error is less than 0.5mm. This high-precision synchronous control can meet the stringent requirements of precise alignment of each layer of materials in the continuous composite process of multi-layer composite materials, effectively improving product quality and production efficiency.
[0027] Design of precise alignment and deviation correction device
[0028] Visual positioning and error compensation algorithm: A high-resolution CCD camera with a resolution of 50μm / pixel and a 75mm telecentric lens is used, and the field of view can fully cover the width of the coil. A coil edge detection algorithm based on feature matching is developed, and the camera sampling frequency is as high as 100Hz, which can quickly and accurately detect the coil edge position, and the positioning error is precisely controlled within ±0.05mm, providing reliable data support for subsequent precise alignment.
[0029] Servo alignment roller design and control: The alignment roller is driven by a linear motor, which has excellent characteristics of high response frequency (100Hz), high displacement resolution (0.1μm) and large maximum stroke (±10mm). Combined with the adaptive control algorithm, it can adjust the alignment roller angle in real time and accurately according to the visual feedback of the coil edge position information, effectively compensate for the lateral position deviation of the coil, ensure the accurate alignment of each layer of the multi-layer composite material during the composite process, and avoid product defects caused by inaccurate alignment.
[0030] Infrared correction sensor design: 940nm infrared LED is used as the light source, and a reflective correction sensor is cleverly designed by pairing silicon photocells and installed on both sides of the coil. The output voltage of the sensor shows an accurate linear relationship with the edge position of the coil, with a sensitivity of up to 0.1mm and a sampling frequency of 1kHz. It can monitor the lateral position change of the coil in real time and feed back the signal to the control system in time so that corresponding correction measures can be taken to further improve the stability and accuracy of the coil transmission process.
[0031] Online quality inspection and feedback control
[0032] Design of online thickness measurement system: It adopts the advanced laser triangulation thickness measurement principle, with a laser beam spot diameter of only 50μm, a Z-axis repeatability of up to 0.5μm, and a measurement range of 0.05-2mm, which can accurately measure the thickness changes of multi-layer composite materials during the production process. The probe is installed on a linear slide rail, which can achieve efficient reciprocating scanning in the width direction of the coil, with a scanning speed of 1m / s and a sampling interval of 1mm. It can comprehensively and quickly obtain coil thickness information, provide a basis for timely adjustment of production process parameters, and ensure the consistency and stability of product thickness.
[0033] Design of online bonding strength test device: With reference to ASTMD3359 standard, an automated scriber is carefully designed to cross-scribe the cured coating to ensure that the depth of the scribe line can accurately reach the substrate. The 180° peeling method is used to test the bonding strength. The tape is peeled off from one end with a pulling force of 10N, and the critical peeling length is recorded in detail, thereby realizing online detection of the bonding strength between layers of multi-layer composite materials. By obtaining the bonding strength data in a timely manner, it is possible to promptly discover possible interlayer bonding problems in the production process, and take corresponding improvement measures to ensure the quality and performance reliability of the product.
[0034] Quality data collection and statistical analysis: Build an industrial Ethernet architecture to achieve real-time data collection, filtering and visualization of various quality inspection equipment such as thickness gauges and tensile gauges, so that quality data in the production process can be clearly seen. At the same time, develop a statistical process control (SPC) module to conduct strict control chart analysis on key quality indicators, which can timely warn and diagnose abnormal conditions in the production process so that corrective measures can be taken in time to ensure that the entire production process is always in a stable and controllable state, effectively improving the product qualification rate and quality stability.
[0035] (III) Optimization of drying and curing process
[0036] Microwave drying technology
[0037] Microwave drying cavity design: A rectangular cavity of WR340 waveguide standard is used, the operating frequency is set to 2.45GHz, the maximum power can reach 1.5kW, and it is equipped with 3 feed ports. The cavity material is 1mm thick aluminum plate, and the inner wall is electroplated with silver to significantly improve the Q value. The coating thickness is not less than 5μm. This cavity design can provide a stable and efficient microwave field environment, which is conducive to the drying and curing of composite materials.
[0038] Optimization of microwave field uniformity: Through professional simulation technology, the feed port position and phase are optimized to make the microwave field present a sinusoidal distribution along the direction of the coil movement, and the unevenness is strictly less than 5%. At the same time, a Teflon mechanical mode stirrer is set on the inner wall of the cavity with a rotation speed of 30rpm to further homogenize the microwave field distribution, ensure that the composite material is heated evenly during the drying and curing process, avoid product quality problems caused by local overheating or overcooling, and improve the overall quality and performance stability of the product.
[0039] Online moisture monitoring and power control: The near-infrared online moisture meter is used, which has a fast response time (less than 100ms), excellent repeatability (better than 0.1%) and a wide measurement range (5%-25%), and can monitor the moisture content in the composite material in real time and accurately. The microwave power closed-loop control system is designed based on the fuzzy PID algorithm, and the magnetron output power is accurately adjusted according to the real-time changes in moisture content to achieve intelligent control of the microwave drying process, while ensuring the drying effect, maximizing energy conservation and reducing production costs.
[0040] Low temperature plasma curing
[0041] Plasma generator design: using capacitively coupled plasma source, the upper electrode uses a porous evenly distributed annular radio frequency electrode, and the lower electrode uses a roller-type transport electrode. The electrode material is made of high-purity graphite, and circulating cooling water is passed inside to ensure that the temperature does not exceed 80°C during continuous operation. This electrode structure and cooling method can ensure the stable operation of the plasma generator and provide a reliable plasma environment for the curing of composite materials.
[0042] Optimization of working gas and chamber pressure: A mixed working fluid of helium and hexafluoroethane is selected, with a volume ratio of He:C2F6 of 95:5 and a gas purity of not less than 99.999%. A capillary array flowmeter is used to accurately control the air intake volume, and the vacuum pump speed is adjusted to maintain the chamber pressure at 100-500Pa. By optimizing the working gas composition and chamber pressure, the activity and stability of the plasma can be effectively improved, the curing reaction of the composite material can be promoted, and the curing effect and product quality can be improved.
[0043] RF power design and impedance matching: The RF power supply uses a 13.56MHz, 5kW solid-state power amplifier and is equipped with an automatic impedance matching network. During operation, the plasma voltage and current waveforms in the chamber are monitored in real time, and the impedance changes are compensated by adjusting the LC circuit to make the reflected power less than 50W, ensuring that the RF power supply can efficiently and stably provide energy to the plasma generator, ensuring the smooth progress of the curing process, while reducing energy loss and improving energy utilization.
[0044] Integrated control of drying, curing and winding
[0045] Synchronous transmission control system design: The microwave drying, plasma curing and winding devices are coaxially linked through servo motors to achieve synchronous speed control, ensuring the continuity and stability of the composite materials during the drying, curing and winding process. The drying and curing section is equipped with a gantry structure and a linear motor module, which can flexibly adjust the relative positions of each device online according to production needs, adapt to the production of multi-layer composite materials with different specifications and different process requirements, and improve the versatility and flexibility of the production line.
[0046] Winding tension closed-loop control: The winding roller is equipped with a magnetic powder brake, which controls the winding tension by precisely adjusting the excitation current, so that the tension fluctuation is less than ±2%. The dancing roller structure is adopted, and the coil accumulation is monitored in real time through the height displacement sensor and fed back to the brake system in time. The winding tension is automatically adjusted according to the change of the coil accumulation, ensuring the tightness and flatness of the coil during the winding process, avoiding the problem of coil slack and wrinkles, and improving the winding quality of the product.
[0047] Finished product winding quality inspection: CCD camera is used to perform 360° imaging inspection on the winding roller, focusing on common defects such as creep, wrinkling, and poor ear shape of the coil, which can timely discover quality problems in the winding process and make corresponding adjustments and treatments. At the same time, the first and last sample sections of each finished roll are automatically sampled and sent to the mechanical properties tester for key mechanical properties tests such as tensile strength and elongation at break to ensure that the quality of the finished product meets the relevant standards and requirements, providing comprehensive and reliable guarantees for product quality control.
[0048] Waste heat recovery and cascade utilization system
[0049] Recycling of waste heat from cooling water of microwave power source: A plate heat exchanger is connected in series at the end of the cooling water pipeline of the magnetron anode to form a secondary circulation system with the clean water pipeline. By reasonably adjusting the frequency of the circulation pump and the opening of the bypass valve, the cooling water temperature is precisely controlled at 45±2℃, and it is used to preheat the surface of the substrate roll, making full use of the waste heat of the cooling water of the microwave power source to achieve energy recovery and reuse, reduce energy consumption in the production process, and improve energy utilization. At the same time, it also helps to increase the initial temperature of the composite material, promote the drying and curing reaction, and further improve production efficiency.
[0050] Energy cascade utilization of plasma electrode cooling system: The plasma electrode cooling circuit is cleverly divided into a high temperature side (60-80℃) and a low temperature side (30-40℃), and a split-range control strategy is adopted. The high temperature side is connected to the infrared preheater on the surface of the functional layer roll, and the high temperature waste heat is used to preheat the functional layer roll, reducing the energy consumption in the subsequent drying and curing process; the low temperature side is used for tempering cooling and water replenishment of the circulating water system, realizing the cascade utilization of energy in the plasma electrode cooling system, maximizing the value of energy utilization, reducing production costs, and also conducive to environmental protection.
[0051] Optimal scheduling of waste heat recovery system operation: Build an energy flow network model, comprehensively consider the complex influencing factors of process parameters, equipment operating conditions, ambient temperature and humidity. Use advanced real-time optimization algorithms to intelligently schedule the waste heat recovery system, and achieve optimal operation of the waste heat recovery system while fully ensuring the production process requirements of multi-layer composite materials, maximize energy utilization, further reduce energy consumption and costs in the production process, and make the entire production process more energy-saving, environmentally friendly, efficient and economical.
[0052] Beneficial effects of the present invention:
[0053] The wet-process multilayer composite material continuous forming process of the present invention effectively solves the problems of poor interlayer bonding, low production efficiency and high energy consumption in existing multilayer composite material technology through innovative nano-level interface treatment technology, efficient roll-to-roll continuous production line design and optimized drying and curing process, significantly improves the performance and production efficiency of composite materials, reduces production costs and energy consumption, and has broad application prospects and important industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0055] Figure 1 It is a schematic diagram of a wet multilayer composite material production line of the present invention;
[0056] Figure 2 A schematic diagram of the nano-interface processing and quality control system of the present invention;
[0057] Figure 3 Schematic diagram of the microwave drying and plasma curing system of the present invention;
[0058] Figure 4 is a schematic cross-sectional view of a multilayer composite material structure of the present invention;
[0059] Figure 5 It is a schematic diagram of the heat recovery and cascade utilization system of the present invention;
[0060] Figure 6 It is a schematic diagram of the production process of the present invention. DETAILED DESCRIPTION
[0061] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0062] It should be noted that the references to "one embodiment", "an embodiment", "an exemplary embodiment", "some embodiments" and the like in the specification indicate that the embodiments described may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it should be within the knowledge of a person skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments (whether or not explicitly described).
[0063] In general, a term can be understood, at least in part, from its use in context. For example, depending, at least in part, on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in the singular sense, or can be used to describe a combination of features, structures, or characteristics in the plural sense. Additionally, the term "based on" can be understood as not necessarily intended to convey an exclusive set of factors, but can instead, depending, at least in part, on the context, allow for the presence of other factors that are not necessarily explicitly described.
[0064] 1. Nanoscale interface processing
[0065] (I) Preparation and spraying of nanosol
[0066] Selection and pretreatment of inorganic nanoparticles
[0067] like Figure 2 As shown, high-purity silicon dioxide (SiO2) and aluminum oxide (Al2O3) nanoparticles prepared by gas phase method are selected, and their particle size is precisely distributed between 20-50nm. In order to improve the compatibility with the polymer, these nanoparticles are placed in a vacuum oven and dried continuously for 4 hours at 120°C to effectively remove the surface adsorbed water.
[0068] Selection and preparation of organic polymers
[0069] Carefully select highly acetalized (99%) polyvinyl alcohol (PVA, degree of polymerization 1700, degree of alcoholysis 88%) and prepare it into a 5wt% aqueous solution. In addition, add a proper amount of crosslinking agent glutaraldehyde to the PVA solution to promote the curing process of the interface layer and significantly improve the bonding strength and water resistance.
[0070] Preparation and homogenization of nanosol
[0071] The pre-treated SiO2 and Al2O3 nanoparticles were uniformly mixed in a mass ratio of 1:1, and then slowly added to the PVA solution, with the solid content strictly controlled at 10wt%. With the help of a high-speed disperser, a shearing operation was performed at a speed of 10,000 rpm for 30 minutes, thus successfully obtaining a uniform and stable nanosol dispersion.
[0072] Design and parameter optimization of automatic spraying device
[0073] like Figure 1 As shown in the figure, the six-axis robot arm guided by machine vision and the multi-axis linkage spray gun are used to achieve precise control of the spraying process on the substrate surface. The spraying process parameters that have been deeply optimized are: the nozzle diameter is set to 0.3mm, the atomization pressure is stabilized at 0.4MPa, the liquid flow rate is controlled at 30mL / min, and the distance between the spray gun and the substrate is maintained at 100mm.
[0074] (ii) Introduction of nanofibers by electrospinning
[0075] Selection and Preparation of Spinning Polymer Materials
[0076] Nylon 6 chips with a melting point of 225° C. are used to prepare a hexafluoroisopropanol solution with a concentration of 15 wt%. At the same time, 1 wt% of hexadecyltrimethylammonium bromide (CTAB) is added as a conductive additive to effectively improve the spinning performance of the solution.
[0077] Design and improvement of electrospinning equipment
[0078] The unique coaxial electrospinning device is designed independently, with the inner layer being the spinning liquid and the outer layer being the high-pressure air, which work together to form a stable composite jet. In addition, a double-ring tube current collecting device is used, in which the inner tube focuses on guiding the fiber deposition, while the outer tube is responsible for sucking out the excess fibers, thereby greatly improving the deposition efficiency.
[0079] Optimization and control of electrospinning process parameters
[0080] The spinning voltage (15-30 kV), receiving distance (10-20 cm) and solution flow rate (0.5-2 mL / h) were optimized through rigorous orthogonal experiments. The jet carving and fiber morphology were monitored in real time using a high-speed camera to ensure that the nanofiber layer had good uniformity and continuity.
[0081] (III) Composite of functional layer and interface layer
[0082] Functional coating formulation design and preparation
[0083] According to different application requirements, we can flexibly choose organic coating systems of UV-curable acrylates and epoxy resins, or inorganic coating systems of ITO and ZnO. We can carefully prepare functional coatings with a thickness of 1-10μm on the PET base film by using the doctor blade method, and use them for subsequent composite processes after drying and curing.
[0084] Optimization of hot pressing process parameters
[0085] The advanced hot roller laminating machine is used to achieve continuous hot pressing laminating operation by precisely controlling the key parameters of roller pressing, temperature and vehicle speed. The optimal laminating conditions are as follows: pressure range is between 1-5MPa, temperature is controlled at 80-130℃, speed is maintained at 1-5m / min, and contact time is maintained at 5-20s.
[0086] Characterization and evaluation of composite interface performance
[0087] like Figure 2 As shown in the figure, high-resolution scanning electron microscope (SEM) and atomic force microscope (AFM) were used to carefully observe the microstructure and roughness of the composite interface. 180° peeling test and tensile shear test were carried out to accurately and quantitatively evaluate the interlayer bonding strength to ensure that it can reach a high standard of more than 20N / cm.
[0088] 2. Design of roll-to-roll continuous production line
[0089] (I) Automatic coil feeding and tension control system
[0090] Design and optimization of unwinding device
[0091] like Figure 1 As shown in the figure, the exquisite combination of electromagnetic powder brake and servo motor is used to achieve precise control of tension, and the tension fluctuation is strictly controlled within ±2%. At the same time, it is equipped with advanced deviation correction device and air expansion shaft to effectively ensure the coaxiality of the coil and the stability of the axial position during the unwinding process.
[0092] Guide roller system design
[0093] The uniquely arranged guide roller group of Archimedean spiral can cleverly realize the 90° turning and S-type tensioning of the coil. The surface of the guide roller is coated with polyurethane elastomer, and its hardness is controlled between ShoreA50-80, which effectively prevents the coil from slipping and being damaged.
[0094] Synchronous transmission and control solutions
[0095] The electronic gear synchronization control system is used to achieve speed synchronization and phase synchronization between the substrate roll and the functional layer roll. The speed synchronization error is less than 0.1%, and the phase synchronization error is less than 0.5mm, which fully meets the stringent requirements of high-precision continuous lamination.
[0096] (II) Design of precise alignment and deviation correction device
[0097] Visual positioning and error compensation algorithm
[0098] The CCD camera has a resolution of up to 50μm / pixel and is equipped with a 75mm telecentric lens, and its field of view can fully cover the width of the coil. A coil edge detection algorithm based on feature matching has been developed, with a camera sampling frequency of up to 100Hz and positioning error accurately controlled within ±0.05mm.
[0099] Design and control of servo registration roller
[0100] The linear motor is used to drive the registration roller, with a response frequency of up to 100Hz, a displacement resolution of 0.1μm, and a maximum stroke of ±10mm. An adaptive control algorithm is designed to adjust the registration roller angle in real time based on visual feedback information to accurately compensate for the lateral position deviation of the coil.
[0101] Design of infrared correction sensor
[0102] The 940nm infrared LED is used as the light source, and the reflective correction sensor is cleverly designed with silicon photocells and installed on both sides of the coil. The sensor output voltage shows an accurate linear relationship with the edge position of the coil, with a sensitivity of up to 0.1mm and a sampling frequency of 1kHz.
[0103] (III) Online quality inspection and feedback control
[0104] Design of online thickness measurement system
[0105] The laser triangulation method is used to measure thickness. The laser beam spot diameter is only 50μm, the Z-axis repeatability is 0.5μm, and the measurement range covers 0.05-2mm. The probe is installed on a linear slide rail, which can achieve efficient reciprocating scanning in the width direction of the coil, with a scanning speed of 1m / s and a sampling interval of 1mm.
[0106] Design of online bonding strength testing device
[0107] With reference to ASTMD3359 standard, the automated scribing device is carefully designed to cross-scribe the cured coating to ensure that the scribing depth can accurately reach the substrate. The 180° peeling method is used to test the bonding strength, peeling the tape from one end with a pulling force of 10N, and recording the critical peeling length in detail.
[0108] Quality data collection and statistical analysis
[0109] Build an industrial Ethernet architecture to achieve real-time data collection, filtering and visualization of thickness gauge and tensile gauge data. Develop a statistical process control (SPC) module to conduct strict control chart analysis of key quality indicators and timely warn and diagnose abnormal working conditions.
[0110] 3. Drying and curing process optimization
[0111] (1) Microwave drying technology
[0112] Microwave drying chamber design
[0113] like Figure 3 As shown, a rectangular cavity of WR340 waveguide standard is used, the operating frequency is set to 2.45GHz, the maximum power can reach 1.5kW, and it is equipped with 3 feed ports. The cavity material is 1mm thick aluminum plate, and the inner wall is electroplated with silver to significantly improve the Q value, and the coating thickness is not less than 5μm.
[0114] Microwave field uniformity optimization
[0115] Through professional simulation and optimization of the feed port position and phase, the microwave field presents a sinusoidal distribution along the direction of the coil movement, and the unevenness is strictly less than 5%. A Teflon mechanical mode stirrer is set on the inner wall of the cavity with a rotation speed of 30rpm to further homogenize the microwave field distribution.
[0116] Online moisture monitoring and power control
[0117] A near-infrared online moisture meter is used, with a response time of less than 100ms, a repeatability better than 0.1%, and a measurement range of 5%-25%. A microwave power closed-loop control system is designed based on the fuzzy PID algorithm to adjust the magnetron output power in real time according to the moisture content.
[0118] (II) Low temperature plasma curing
[0119] Plasma generator design
[0120] It uses a capacitively coupled plasma source, a porous and uniformly distributed annular radio frequency electrode for the upper electrode, and a roller-type transport electrode for the lower electrode. The electrode material is made of high-purity graphite, and circulating cooling water is passed inside to ensure that the temperature does not exceed 80°C during continuous operation.
[0121] Working gas and chamber pressure optimization
[0122] A mixed working fluid of helium and hexafluoroethane is selected, with a volume ratio of He:C2F6 of 95:5 and a gas purity of not less than 99.999%. A capillary array flowmeter is used to accurately control the gas intake volume, and the vacuum pump speed is adjusted to maintain the chamber pressure at 100-500Pa.
[0123] RF Power Design and Impedance Matching
[0124] The RF power supply uses a 13.56MHz, 5kW solid-state power amplifier equipped with an automatic impedance matching network. The plasma voltage and current waveforms in the chamber are monitored in real time, and the LC circuit is adjusted to compensate for impedance changes. The reflected power is less than 50W.
[0125] (III) Integrated control of drying, curing and winding
[0126] Design of synchronous transmission control system
[0127] The microwave drying, plasma curing and winding devices are coaxially linked through servo motors to achieve synchronous speed control. The drying and curing section is equipped with a gantry structure and a linear motor module to adjust the relative positions of each device online.
[0128] Winding tension closed loop control
[0129] The winding roller is equipped with a magnetic powder brake, which controls the winding tension by adjusting the excitation current, and the tension fluctuation is less than ±2%. The dancing roller structure is adopted, and the coil accumulation is monitored in real time through the height displacement sensor and fed back to the braking system.
[0130] Finished product winding quality inspection
[0131] The CCD camera is used to perform 360° imaging inspection on the winding roller, focusing on defects such as creep, wrinkling, and poor ear shape of the coil. The first and last samples of each finished roll are automatically sampled and sent to the mechanical properties tester for tensile strength and elongation at break tests.
[0132] (IV) Waste heat recovery and cascade utilization system
[0133] Microwave power source cooling water waste heat recovery
[0134] like Figure 5 As shown in the figure, a plate heat exchanger is connected in series at the end of the magnetron anode cooling water pipeline to form a secondary circulation system with the clean water pipeline. By adjusting the circulation pump frequency and the bypass valve opening, the cooling water temperature is accurately controlled at 45±2℃ for preheating the substrate roll surface.
[0135] Energy cascade utilization of plasma electrode cooling system
[0136] The plasma electrode cooling circuit is divided into a high temperature side (60-80℃) and a low temperature side (30-40℃), and a split-range control strategy is adopted. The high temperature side is connected to the infrared preheater on the surface of the functional layer roll, and the low temperature side is used for tempering cooling and water replenishment of the circulating water system.
[0137] Optimal operation and scheduling of waste heat recovery systems
[0138] Build an energy flow network model, comprehensively consider process parameters, equipment operating conditions, ambient temperature and humidity and other influencing factors. Use real-time optimization algorithms to schedule the waste heat recovery system, while fully ensuring process requirements and maximizing energy utilization.
[0139] Embodiment 1:
[0140] Preparation and application of wet multilayer composite materials
[0141] Objective: To prepare a wet-process multilayer composite material with excellent interfacial bonding strength and water resistance, and to test its application performance in electronic product housings.
[0142] Implementation steps:
[0143] Nanosol preparation:
[0144] like Figure 2 As shown, SiO2 and Al2O3 nanoparticles prepared by a gas phase method with a particle size of 20-50 nm were selected and placed in a vacuum oven at a temperature of 120°C for 4 hours to remove moisture adsorbed on the surface.
[0145] A 5 wt % PVA aqueous solution was mixed with a cross-linking agent, glutaraldehyde, at a mass ratio of 1:1 to prepare a PVA solution.
[0146] The mixture was sheared at 10,000 rpm for 30 minutes using a high-speed disperser to obtain a uniform SiO2 / Al2O3 / PVA nanosol.
[0147] Electrospinning treatment:
[0148] Nylon 6 chips were dissolved in hexafluoroisopropanol solution with a concentration of 15 wt %, and 1 wt % of CTAB was added.
[0149] The spinning was carried out using a self-designed coaxial electrospinning device with a spinning voltage of 25 kV, a receiving distance of 15 cm, and a solution flow rate of 1 mL / h. A high-speed camera was used to monitor the fiber morphology in real time to ensure that the fiber layer was uniform and continuous.
[0150] Functional layer composite:
[0151] UV-curable acrylate was selected as the functional coating material and coated on the PET base film using a doctor blade method with a thickness controlled at 5 μm.
[0152] A hot press laminating machine was used for the laminating operation, with the temperature set at 100°C, the pressure set at 3 MPa, the laminating speed at 3 m / min, and the contact time at 10 s.
[0153] Performance Test:
[0154] like Figure 2 As shown, scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to observe the microscopic morphology of the composite interface and analyze its roughness and interface bonding strength.
[0155] A 180° peel test was conducted and the interlayer bonding strength was measured to be 25N / cm, meeting the high strength requirements.
[0156] Application effect:
[0157] This wet-process multi-layer composite material has been successfully applied to the casing of electronic products. It has excellent water resistance and mechanical strength, and can effectively improve the durability and impact resistance of the casing.
[0158] Embodiment 2:
[0159] Design and application of roll-to-roll continuous production line
[0160] Objective: To design and optimize a roll-to-roll continuous production line for large-scale production of nanocomposites, ensuring high efficiency and stability during the production process.
[0161] Implementation steps:
[0162] Automatic feeding and tension control:
[0163] like Figure 1 As shown, the electromagnetic powder brake and servo motor are combined to control the web tension, ensuring that the tension fluctuation is strictly controlled within ±2%.
[0164] The air shaft and the deviation correction device are used to maintain the coaxiality of the coil and ensure the uniformity of the substrate surface.
[0165] Guide roller system design:
[0166] The Archimedean spiral guide roller group is used to prevent the coil from slipping or being damaged during the turning and tensioning process. The surface of the roller group is coated with polyurethane elastomer, and the hardness is controlled at Shore A60, which increases the wear resistance of the roller group and the contact performance with the coil.
[0167] Precise alignment and correction:
[0168] Equipped with a CCD camera, it detects the edge position of the coil in real time through a feature matching algorithm, and the positioning error is controlled within ±0.05mm to ensure accurate alignment of the coil.
[0169] The servo registration roller driven by a linear motor is used to adjust the registration roller angle in real time in combination with visual feedback information to ensure that the lateral deviation of the coil is within a reasonable range.
[0170] Online quality inspection:
[0171] The thickness gauge using the laser triangulation method has a measuring range of 0.05-2mm and an accuracy of 0.5μm, ensuring the uniformity of the thickness of each layer of coating.
[0172] An online bonding strength testing device is set up to carry out peeling tests in accordance with ASTMD3359 standard to ensure that the interlayer bonding strength of each batch of products reaches above 20N / cm.
[0173] Application effect:
[0174] Through the optimized roll-to-roll production line, high-precision continuous production is achieved. The product performs well in quality control, the production efficiency is increased by 30%, and the coating performance meets the requirements of high strength and water resistance, making it suitable for large-scale production of nano-composite materials.
[0175] Embodiment 3:
[0176] Optimization and application of microwave drying technology
[0177] Objective: To optimize the microwave drying process and improve the drying efficiency and uniformity of wet-process multilayer composite materials.
[0178] Implementation steps:
[0179] Microwave drying chamber design:
[0180] like Figure 3 As shown, the design uses a rectangular cavity of the WR340 waveguide standard, with an operating frequency of 2.45GHz and a maximum power of 1.5kW. The cavity material is a 1mm thick aluminum plate with a silver-plated inner wall to increase the Q value.
[0181] Equipped with 3 feed ports to ensure even distribution of microwave energy and improve drying efficiency.
[0182] Microwave drying process control:
[0183] The coated substrate was passed through a microwave drying chamber, the temperature in the chamber was set at 80°C, and a stable working environment was maintained by an automated temperature control system.
[0184] The microwave power was set to 1 kW and the drying time was controlled within 3 minutes to ensure that the coating was evenly dried without overheating.
[0185] The mechanical strength test of the dried composite material was carried out, and the interlayer bonding strength was measured to be 22N / cm, which met the requirements.
[0186] Use an infrared thermal imaging camera to monitor the drying process to ensure that the material surface temperature is uniform and does not fluctuate.
[0187] Application effect:
[0188] The optimization of microwave drying process significantly improved the drying efficiency, reduced the drying time, reduced energy consumption, and ensured the quality stability of wet-process multilayer composite materials after drying.
[0189] The present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention. In order to make the public have a thorough understanding of the present invention, specific details are described in detail in the following preferred embodiments of the present invention, but those skilled in the art can fully understand the present invention without the description of these details. In addition, in order to avoid unnecessary confusion about the essence of the present invention, well-known methods, processes, procedures, components and circuits are not described in detail.
[0190] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0191] The present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention. In order to make the public have a thorough understanding of the present invention, specific details are described in detail in the following preferred embodiments of the present invention, but those skilled in the art can fully understand the present invention without the description of these details. In addition, in order to avoid unnecessary confusion about the essence of the present invention, well-known methods, processes, procedures, components and circuits are not described in detail.
[0192] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A continuous molding process for a wet multilayer composite material, characterized in that: The process includes the following steps: A layer of nanosol is sprayed on the surface of the substrate, wherein the nanosol includes high-purity silicon dioxide (SiO2) and aluminum oxide (Al2O3) nanoparticles with a particle size range of 20-50nm, mixed with a polyvinyl alcohol (PVA) solution and homogenized; Using electrospinning technology to introduce nanofibers into the nanosol to form a nanofiber layer, the nanofibers are composed of nylon 6 and cetyltrimethylammonium bromide (CTAB) solution; In the nanostructure, the functional layer and the substrate layer are compounded by a hot pressing process, and the functional layer is a coating that is either UV-cured or epoxy-cured; After drying and curing, a continuously produced multi-layer composite material is formed.
2. The process according to claim 1, wherein the nanosol is a mixture of SiO2 and Al2O3 nanoparticles in a mass ratio of 1:1, and the solid content of the nanosol is controlled at 10wt%.
3. The process according to claim 1, wherein the concentration of the PVA solution is 5 wt%, and a cross-linking agent glutaraldehyde is added to the solution to promote the curing of the interface layer.
4. The process according to claim 1, wherein the electrospinning step uses a hexafluoroisopropanol solution with a concentration of 15 wt%, and 1 wt% of CTAB is added to the solution as a conductive additive.
5. The process according to claim 1, wherein the spraying process uses a six-axis robotic arm and a multi-axis linkage spray gun guided by machine vision, the nozzle diameter is 0.3 mm, the atomization air pressure is 0.4 MPa, the liquid flow rate is 30 mL / min, and the distance between the spray gun and the substrate is 100 mm.
6. The process according to claim 1, wherein the hot pressing composite process is carried out at a temperature range of 80-130°C, a pressure range of 1-5 MPa, a vehicle speed of 1-5 m / min, and a contact time of 5-20 s.
7. The process according to claim 1, wherein the interface layer of the composite material is subjected to morphological analysis using a high-resolution scanning electron microscope (SEM) and an atomic force microscope (AFM), and the interlayer bonding strength of the peeling test reaches above 20 N / cm.
8. A roll-to-roll continuous forming production line, characterized in that: include: Automatic feeding and tension control system, using electromagnetic powder brake and servo motor, tension fluctuation is controlled within ±2%, equipped with deviation correction device and pneumatic shaft; The guide roller system adopts Archimedean spiral roller group and is coated with polyurethane elastomer to prevent the coil from being damaged; The visual positioning and error compensation system uses a CCD camera and feature matching algorithm to control the positioning error within ±0.05mm; The online quality inspection system, including a laser thickness gauge and an automated bond strength tester, collects data in real time and performs statistical analysis through an industrial Ethernet architecture.
9. The production line according to claim 8, wherein the online thickness measurement system adopts laser triangulation method, with a measurement range of 0.05-2mm, a repeatability of 0.5μm, a scanning speed of 1m / s, and a sampling interval of 1mm.
10. The production line according to claim 8, wherein the online bonding strength testing device adopts a 180° peeling method and applies a 10N pulling force during the test.
Citation Information
Patent Citations
Device and method for preparing multi-layer composite nanofiber proton exchange membrane
CN105280939A
Ultra-high-flux nano-fiber waterproof gas-permeable membrane and preparation method thereof
CN107326653A
High-precision prepreg tape winding machine structure and control method
CN115385141A
Degradable oiling agent for nylon high-temperature-resistant anti-yellowing spinning and preparation method thereof
CN115897216A
Self-cleaning nanofiber composite membrane and preparation method thereof
CN117818176A
Cited By
Coating machine control method and coating machine operation system
CN120587076A